ANALISIS KOLABORASI DALAM PENGELOLAAN DESA WISATA: KASUS DI DESA NGANJAT KECAMATAN POLANHARJO KABUPATEN KLATEN - Rendy Gilang Permana; Teuku Afrizal; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Tourism villages are one of the applications of community-based and sustainable tourism development. It is hoped that through the development of the tourism village there can be equity in accordance with the concept of sustainable tourism development. Nganjat Village is a tourism village located in Polanharjo District, Klaten Regency. The tourism development process in Nganjat Village has not yet seen significant progress. The role of stakeholders in the implemented training system has not gone well. This study used qualitative research methods. The purpose of this study is to analyze the process of collaboration in the management of tourist villages and their driving and inhibiting factors. The theory used is the collaborative process theory according to Ansell and Gash. The result of the research is that the process of implementing the laser is still not going well because of less effective communication and less optimal roles between stakeholders. Factors driving collaboration are community empowerment, job creation, moments to unite village communities, and providing a platform for Karang Taruna to participate in supporting village progress. The inhibiting factors are the unstable condition of Karang Taruna, ineffective communication, the absence of Bumdes, and the lack of stakeholders who are experts in managing sustainable tourism. The researcher recommends collaborating with academics who are experts in the field of sustainable tourism management and improving aspects of communication between stakeholders.